Deep, Surface, or Both? A Study of Occupational Therapy Students’ Learning Concepts - Tore Bonsaksen (Occupational Therapy International, 2018)
Background. Students’ conceptualization of learning has been associated with their approaches to studying. However, whether students’ learning concepts are associated with their personal characteristics is unknown. Aim. To investigate whether sociodemographic, education-related, and personal factors were associated with the learning concepts of Norwegian occupational therapy students. Methods. One hundred and forty-nine students (mean age 23.9 years, 79.2% women) participated in the study. The employed self-report questionnaires included the Approaches and Study Skills Inventory for Students, the Rosenberg Self-Esteem Scale, and the General Self-Efficacy Scale. Differences between student cohorts were analyzed with one-way analyses of variance and χ2 tests, whereas factors associated with the students’ learning concepts were analyzed with bivariate correlation and linear regression models. Results. The students’ mean scores on the deep and surface learning concept scales were similar. Spending more time on the independent study was associated with having higher scores on the unidimensional learning concept measure. Conclusions. The students’ learning concept appears to encompass a surface concept as well as a deep concept of learning, and the two ways of conceptualizing learning were positively related to each other. Over time, a mature deep concept may add to, rather than replace, a basic surface concept of learning.